Gender difference, anxiety and the fear of crime, 1995 - Hollway, Wendy (UK Data Service, 2003)
This research focused on crime and its relation to risk of victimisation and the suggestion that high-risk groups, in particular, young men, report lower fear than low-risk groups, in particular, older women. The notion of anxiety as a mediating influence in the relationship between risk of victimisation and fear of crime was examined. Through a set of face-to-face interviews, the research found that the effect of risk figured prominently in interviewee's accounts of their fear of crime and their previous victimisation. They not only positioned themselves as more or less at risk but more actively were recurrently engaged in more or less ‘risky’ practices. The research suggests that the relations between risk and fear of crime cannot be understood without theorising the multiple meanings attaching to a person’s identity which become invested with anxiety. The data consists of interview transcripts with men and women living on estates where the incidence of crime was either high or low. The interviews aimed to understand the differences in fear of crime among different social groups, integrating demographic characteristics, analyses of gender, ethnicity and age.